Ocupaç\~ao do setor de turismo no Brasil: Análise da ocupaç\~ao nas principais acts nos estados, regi\~oes e Brasil - Margarida Hatem Pinto Coelho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– This document is based on a series of studies and researches that have been developed by Ipea, since 2003, regarding the labor market in the tourism sector. These studies are aimed at subsiding public policy elaboration, planning and evaluation of this sector as well as its social and economic impact at the federal, regional, and state levels. It updates and supplements the Discussion Paper No. 1320, issued in 2008, in the matters related to the state level. The current paper presents, for Brazil as a whole and for its regions and states the main results of such studies in terms of the labor force occupied in the so-called tourism characteristic activities: Hotels and similar, Restaurants and similar, Travel Agencies, Transport services, Transport Equipment Rental, Transport supporting services, Cultural Services. The theme is put in context with a brief explanation of how the studies were developed, followed by the results which were obtained. Information is analyzed, in totals, for the 27 states of the Brazil and also to its respective five regions, with data concerning the number of occupation in the formal segment, the relative participation of each activity in the total employment rate generated by tourism, the formality and evolution of such activities in the period between December 2002 and December 2008. The information is presented separately for the States of S\~ao Paulo, Rio de Janeiro, and Bahia, which account for 39% of the occupation by tourism in Brazil. The results for the formal segment for the states of Paraná, Goiás and Pará, are also shown. The paper ends presenting a summary for formal and informal occupation considering the tourism sector in Brazil as a whole and its regions. Attached are the data for all the units of the Brazilian federation, for the regions and the country.
Keywords: J49; 330; Tourismuswirtschaft; Arbeitsmarkt; Arbeitskräftepotenzial; Brasilien